Growth, Mortality, Exploitation Rate, and Recruitment of Blood Clam (Anadara granosa) in the Rangsang Barat Waters, Riau Province - Efriyeldi Efriyeldi; Ronal Kurniawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Growth, mortality, exploitation rate, and recruitment of Anadara granosa cockle in Rangsang Barat coastal waters were studied from July to October 2019. The objective of this research was to study growth. mortality. exploitation rate and recruitment of A granosa cockle. Sampling was done monthly at three main stations. The cockle collected from plot 1 x 1 m2 on quadrat transect. The result showed that the asymptotic length (L∞) of P. acutidens was 30.45 mm. annual growth coefficient (K) was 0.83 per year. The total mortality (Z) was 4.46 per year. natural mortalities (M) was 1.60 per year and fishing mortalities (F) was 2.86 per year. The rate of exploitation (E = 0.64) of blood clams in Rangsang Barat waters has begun to threaten sustainability. The recruitment occurred every month. the peaks occurred in July (13.83 %) dan August (13.08 %).